TODA-YAMAMOTO CAUSALITY TEST BETWEEN ENERGY CONSUMPTION AND ECONOMIC GROWTH: EVIDENCE FROM A PANEL OF MIDDLE EASTERN COUNTRIES. - Ai̇mer, Nagmi; Di̇lek, Serkan (Journal of Empirical Economics and Social Sciences, Bandirma Onyedi Eylul University, 2021)
In this paper, we examine the intertemporal causal relationship between economic growth and energy consumption in the selected sixteen the Middle East and North Africa countries by annual data (1985–2016). Unlike the majority of the previous studies and as an alternative to the conventional method of having the same integration of time series and large samples, the Autoregressive Distributed Lag (ARDL) bounds test approach and causality analysis were applied by Toda & Yamamoto (1995). The results of the bounds test show that there is a stable long run relationship between economic growth and total final energy consumption. On the other hand, the results of the causality test, show that there is a unidirectional causal flow from economic growth to total energy consumption that energy conservation policies may not unfavourable effects on economic growth. Overall, these countries meet the conservation hypothesis which means that the causal aspect is unidirectional from economic growth to total final energy consumption and that energy conservation policies will have little or no negative impact on growth in these energy-dependent countries.
Keywords: Energy consumption; Economics; Ekonomi; 8. Economic growth; 1. No poverty; 7. Clean energy